(untitled) (Quinto Sol, 2015)
This article analyzes the first reorganization process carried on Peronism after the military coup of 1955. The initiative took shape through the formation of the Justicialist Party, party organization that was formed in late 1958 and ran until March 1960. The examination was performed considering the various political actors involved, causing tensions and their relation to the national political scene.